Formulasi Tablet ODT Natrium Diklofenak Menggunakan Kombinasi Disintegran Pati Kacang Hijau dan Pati Kentang : ODT FORMULATION OF DICLOFENAC SODIUM COMBINED WITH MUNG BEAN STARCH (Vigna radiata (L.) R.Wilczek) AND POTATO STARCH (Solanum tuberosum L.) AS A DISINTEGRANT - rizka; Gabena Indrayani Dalimunthe; Minda Sari Lubis; Rafita Yuniarti (LPPM Universitas Abdurrab, 2025)
Green beans and potatoes are plants that have very high starch purity which can be used as excipients, especially disintegrants in tablet formulations. Diclofenac sodium is one of the most frequently prescribed anti-inflammatories and is consumed by many elderly patients. Meanwhile, elderly patients often have difficulty swallowing conventional tablets. Orally disintegrating tablet (ODT) is a solid dosage form that quickly disintegrates when placed on the tongue and is expected to be a solution for patients who have difficulty swallowing conventional tablets. This research aims to formulate Orally disintegrating Diclofenac Natrium tablets with a combination of disintegrating ingredients, namely potato starch and green bean starch and to obtain the disintegrating ingredient composition in the optimum formula. Orally disintegrating tablets are made using the direct compression method with a tablet weight of 200 mg. Tablet preformulation tests were carried out including flow time tests, angle of repose tests, bulk density tests and compressibility index tests. And the tablet physical quality evaluation tests include weight uniformity test, hardness test, firmness test, disintegration time test, wetting time test, and disintegration time test in the mouth. The research results showed that the preparation of Orally disintegrating Diclofenac Natrium tablets met the requirements for good physical properties. The fastest tablet disintegration time test was produced by formula 6 and the longest disintegration time test was produced by formula 1. Mung bean starch and potato starch can be used as disintegrants in the formulation of Orally disintegrating Diclofenac Sodium tablets. Keywords : Orally Disintegrating Tablets, Diclofenac Sodium, Green beans, ..Potatoes, Disintegrant